Singularidades das estruturas agrícolas da regi\~ao Centro-Oeste entre 1995 e 2021: Um olhar por intermédio dos indicadores regionais de localizaç\~ao e especializaç\~ao - Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The objective of this investigation was to characterize the agricultural structures in the center of the country, in their multiscalar forms, with regard to their location and specialization aspects. For all these reasons, there is a strong specialization in soybean, corn, sugar cane and cotton in the Midwest region, but with a different degree of specialization between them. The crop that presents a pattern closer to that verified for the reference region was soybean, but followed by corn, cotton and sugar cane. On the other hand, the Herfindahl-Hirschman Index highlighted that the soybean crop was also the one that presented the lowest concentration of production at the level of municipalities in the Center-West region vis-à-vis the crops of corn, sugar cane and cotton. Finally, the micro-regions of Rosario do Oeste, Norte Araguaia, Alta Floresta, Paranatinga were those that presented the highest degree of restructuring in their agricultural structures between the years 1996 and 2021.
Keywords: R11; 330; agricultural structure; export crops; Midwest